Exploring the Factors Affecting Skilled Birth Attendance in Lumbini Province - Devkota, Bijaya Mani; Acharya, Suresh (Tri-Chandra Journal of Anthropology, 2025)
Skill Birth Attendance (SBA) is an important intervention for the reduction of maternal and newborn mortality, especially applicable for third-world countries like Nepal and the neighboring countries in its region. Despite the national efforts, there are still regional disparities in accessing SBAs, especially in case of Lumbini province where sociological, demographic, and economic barriers are considered prominent. This study attempts to figure out the factors influencing the utilization of SBA in the Lumbini Province based on recent national survey data. The Cross-sectional analytical study conducted using data from the Nepal Demographic and Health Survey (NDHS) 2022. It used a two-stage stratified sampling design covering 14,845 women aged 15–49. A logistic regression was applied to assess the significant predictors influencing the use of SBA. The SBA services were utilized more by younger mothers (20-24), first-time mothers, educated women, urban residents, and women from wealthier households. However, the logistic regression revealed that an increasing birth order had increased the odds of not going to SBA services (OR = 0.16, p < 0.01). Economic status could be considered a strong variable in predicting positive utilization. Most importantly, women in the richest quintile had about 10 times higher odds of SBA service use than those in the poorest (OR = 9.84, p < 0.1). Other included factors such as education, caste/ ethnicity, religion, and rural residence had lost their significance after adjustment. Economic status and birth order are important determinants of SBA utilization in Lumbini Province, which shows the persistence of inequality in accessing maternal healthcare. There should be formulated policies directed at alleviating poverty among and supporting multiparous women to improve SBA utilization and promote maternal health results in Lumbini Province.